Pengaruh Video terhadap Peningkatan Pengetahuan Cuci Tangan Pakai Sabun dalam Pencegahan COVID-19 pada Siswa Sekolah Dasar - Risti Evi Yuniastuti; Marsiana Wibowo (Jurnal Cakrawala Promkes, 2022)
Background: Hands are parts of the human body that are agents of disease transmission. It is known that the transmission of COVID-19 is through hands. Therefore, the way to prevent the transmission of COVID-19 is by washing hands with soap (CTPS). Moreover, at Watupecah State Elementary School there has never been any research related to CTPS and students' lack of knowledge regarding CTPS. So, the school during the COVID-19 pandemic needs to increase knowledge about CTPS. One way to increase knowledge is by providing health education related to CTPS with video media through its strong visualization. The purpose of the study was to analyze the effect of video media on the level of knowledge of handwashing with soap in preventing COVID-19 among students at the Watupecah State Elementary School Tempel Sleman. Methods: The study used a Quasi-Experimental research design using a one-group pretest-posttest design. The 45 students in this study were from Watupecah State Elementary School's 4th and 5th grades. Total sampling was used to acquire data. The Wilcoxon Sign Ranks Test was performed to analyze the data. Results: Before receiving video media intervention, 17 people (37.8%) had a high level of knowledge, which climbed to 36 persons after receiving video media intervention (80 percent ). The Wilcoxon Sign Ranks test yielded a p-value of 0.000, which is significantly lower than the p-value of 0.05, with Ha accepted and Ho rejected. Conclusion: Students at the State Elementary School of Watupecah Tempel Sleman have an influence of video media on their level of awareness of handwashing with soap in the prevention of COVID-19.